2022
DOI: 10.1177/00027642221132185
|View full text |Cite
|
Sign up to set email alerts
|

A Social Diagnosis of Digitally Mediated COVID-19 Trauma

Abstract: Using a social diagnosis approach to COVID-19-related trauma, this research bridges the fields of sociology of medicine, disaster response, digital sociology, and digital divides. Bringing these literatures into dialogue, we problematize the digitally mediated trauma ensuing from COVID-19. We unpack two emergent media pathways or channels to a social diagnosis of trauma specific to sharp increase in reliance on digital media occasioned by the pandemic. The research advances the theoretical concept of the digit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Some researchers show correlations between increased screen time, particularly social media, and decreased psychological well-being ( Keles et al, 2020 ; San Juan et al, 2022 ; Twenge & Campbell, 2018 ). Many of these negative patterns were potentially exacerbated by COVID-19 lockdowns that necessitated heavy reliance on digital media use; these patterns may be indicative of the digital trauma paradox, in which oversaturation from toxic digital content may act as a social determinant of health ( Chiaraluce et al, 2022 ). More specifically, the COVID-19 pandemic highlighted the ways in which trauma can be digitally mediated, and therefore, may help to understand the decrease in mental health and well-being.…”
Section: Gen Z Remote Work and Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers show correlations between increased screen time, particularly social media, and decreased psychological well-being ( Keles et al, 2020 ; San Juan et al, 2022 ; Twenge & Campbell, 2018 ). Many of these negative patterns were potentially exacerbated by COVID-19 lockdowns that necessitated heavy reliance on digital media use; these patterns may be indicative of the digital trauma paradox, in which oversaturation from toxic digital content may act as a social determinant of health ( Chiaraluce et al, 2022 ). More specifically, the COVID-19 pandemic highlighted the ways in which trauma can be digitally mediated, and therefore, may help to understand the decrease in mental health and well-being.…”
Section: Gen Z Remote Work and Covid-19mentioning
confidence: 99%
“…We bring the concept of Gen T into dialogue with our prior research on COVID-19 that has shown the value of using a social diagnosis approach. We identify the ways in which digital engagements can function as a social determinant of health with a variety of impacts on well-being ( Chiaraluce et al, 2022 ; Robinson et al, 2021 ).…”
Section: A Social Diagnosis Approach To the Seven Cs Of Creative Conf...mentioning
confidence: 99%
See 1 more Smart Citation